Economic and Psychological Aspects of Poverty (Eurasian Journal of Learning and Academic Teaching, 2023)
The paper identifies and describes two conceptual approaches to defining the phenomenon of poverty - absolute and relative. Some historical stages in the study of poverty, as well as psychological and value foundations of the subculture of the poor are considered. The experience of recent research in this field and new approaches to poverty alleviation are analysed.